About Game-Satires - Jankowski, Filip Fabian (Replay. The Polish Journal of Game Studies, 2022)
This paper proposes introducing a new category to describe certain digital games – “game-satire” (“gropowiastka”) – similar to literary philosophical satires. The author takes as his point of departure the term “game-story” (“gropowieść”) proposed by Tomasz Z. Majkowski, which usually refers to games that are rich in meaning and leave the player with a large margin of freedom. In contrast to the game-stories, the game-satires impose both the order of overcoming challenges and a particular flow of narration; the vision of the gameworld suits the thesis assumed by the creators. The term “game-satires” can include, for example, adventure games, autobiographical games, newsgames and “walking simulators.” The proposed concept would make it possible to challenge the rigid division of ludic software into “games” and “non-games” and more easily incorporate them into artistic discourse.